1990
DOI: 10.1016/0266-7681(90)90089-m
|View full text |Cite
|
Sign up to set email alerts
|

The Herbert Screw for Delayed and Non-Union of Scaphoid Fractures: A Review of Fifty Cases

Abstract: The results of treatment using the Herbert screw in 50 consecutive patients with delayed or established non-union of the scaphoid are reported. 14% of these fractures failed to unite after operation and a further 20% required prolonged protection, uniting within six months. There were significant technical problems in 28% of operations. A bone graft was only used when there was significant collapse of the scaphoid (52%) and the cases without graft did just as well. Overall, the results do not support the view … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
7

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 8 publications
1
26
1
7
Order By: Relevance
“…The immobilization period in our series is not too long when compared with those described above. The technique of Herbert screw fixation requires skill and experience [5,15]. The results reported do not support the view that Herbert screw fixation with bone grafting is a significant advance over Russe grafting in terms of union rate [1,4,5,15].…”
Section: Discussioncontrasting
confidence: 39%
“…The immobilization period in our series is not too long when compared with those described above. The technique of Herbert screw fixation requires skill and experience [5,15]. The results reported do not support the view that Herbert screw fixation with bone grafting is a significant advance over Russe grafting in terms of union rate [1,4,5,15].…”
Section: Discussioncontrasting
confidence: 39%
“…The patients treated with wedge grafting had a similar time from injury to operation as our series, and there was a success rate of 75%, better than with inlay grafting. Radford, Matthewson and Meggitt (1990) reported 50 patients treated for delayed union and nonunion with Herbert screws. The rate of union was 79% for the nonunion group although only 58% had bone grafts.…”
Section: Resultsmentioning
confidence: 99%
“…1,6,10,22,23,[25][26][27][28][29][30][31][32] More recent reports have shown some technical difficulties of screw insertion. 1,3,6,9,27,33 These technical difficulties are particularly addressed in cases of nonunited scaphoid wrist fractures that have palmar bone deficiency when screw insertion is by the palmar route. 11,34 Buttress plate Muller et al,12 in their text, Manual of Internal Fixation, stated that, "If the fracture is in the metaphysis and the cortical shell has been comminuted, the compressive forces tend to lead to an axial deviation or bending.…”
Section: Screw Fixationmentioning
confidence: 99%
“…[1][2][3][4] At present, agreement has been reported about the 3-step principle of management of the nonunited scaphoid wrist collapse with DISI: open reduction, length restoration by interpositional anterior wedge grafting, and internal fixation by screw. [3][4][5][6][7][8][9][10] Although it was found that Herbert screw fixation gave a higher success rate in achieving bony union with better functional results, the technical difficulty and the need to release the scaphotrapezial ligament were addressed by some surgeons. 1,3,11 From the mechanical standpoint, in comparison to compression screws, the buttress plate provides improved methods of internal fixation for a collapsed fracture.…”
mentioning
confidence: 95%